ANALISIS MINAT BELAJAR SISWA SD MENGGUNAKAN PEMBELAJARAN OPEN ENDED - Anggraini Ani (Jurnal Muara Pendidikan, 2020)
The background of this research is the low learning interest of students at SD Negeri No. 166 / II Tirta Mulya in learning mathematics. One reason is the learning provided by teachers who are less attractive. Indications of the low student interest in learning can be seen when learning takes place, many students are making a fuss by themselves, joking with participation, looking at the outside environment and when the teacher provides a stimulus to ask questions, no student is appointed to try. With the existing considerations, efforts can be made by doing better learning. One of the things that can be done is to use open ended learning. With this learning, students are happy because they are challenged to solve many answers. This type of research in this research is a qualitative descriptive study. The instrument used consisted of a questionnaire of learning interest. Data were analyzed by describing the results of the questionnaire. The results of this study are to provide learning that ends, student learning interest in accordance with the high category.